DETERMINAN KEPUTUSAN SISWA BOMBANA MEMILIH PERGURUAN TINGGI: STUDI UNIVERSITAS SAINS ISLAM AL MAWADDAH WARRAHMAH KOLAKA - Anjasmara; Andi Faisal; Ade Saputra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study analyzed the factors influencing the decisions of twelfth-grade students from MA, SMA, and SMK in Bombana Regency in choosing a higher education institution, with a case study of Universitas Sains Islam Al Mawaddah Warrahmah Kolaka (USIMAR). The study employed an explanatory quantitative approach involving 114 respondents and applied multiple linear regression analysis. The variables examined included accreditation, economic factors, social factors, promotion and campus image, and religiosity. The results indicated that, simultaneously, all variables significantly influenced students’ decisions, with an R² value of 0.817. Partially, economic, social, and religiosity factors had a significant effect, whereas accreditation as well as promotion and campus image did not have a significant effect. Social factors were identified as the most dominant determinant influencing students’ decisions to choose USIMAR Kolaka.